Personal data protection and access to information: interfaces of Civil Society role in Brazilian legislative process - Farranha Santana, Ana Claudia; Borsio Bataglia, Murilo; Nunes Lopes Espiñeira Lemos, Amanda (UNIO – EU Law Journal, 2021)
The relationship between access to information and personal data protection leads to the relativization of transparency under the argument of a false tradeoff between these two concepts. Based on that, this study’s objective is to understand the role of civil society movements in maintaining the rights of access to information and personal data protection. This research made a qualitative analysis, with a documentary survey and bibliographic review of the main categories presented in the Executive-Legislative relationship and in the theme of advocacy. We observe the role of civil society lobby groups in the Brazilian Access to Information Law legislative process, between 2003 and 2011, and the Brazilian Data Protection Act, between 2012 and 2018, perceive the change of these groups with the foundation of Rights in Network Coalition, in 2016. As a result, the active participation of Civil Society in public hearings has intensified increasingly in public hearings since 2018, specifically on the LGPD, while LAI had participation of civil society in the body’s scope institutionalized.